1998
DOI: 10.1111/j.1440-1746.1998.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered biliary bilirubin profile in patients with persistent hyperbilirubinaemia after hepatic resection: Analysis of bile bilirubin subfractions by high‐performance liquid chromatography

Abstract: Subfractions of bilirubin in bile, obtained via biliary drainage tubes from 23 patients who had undergone radical surgery for bile duct cancer, were analysed by high-performance liquid chromatography for 14 days after surgery. Five principal conjugated bilirubins were resolved: bilirubin diglucuronide (BDG); bilirubin monoglucuronide monoglucoside (BGG); bilirubin monoglucuronide monoxyloside (BGX); and two isomers of bilirubin monoglucuronide. After surgery, depression in concentration of BDG and elevation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…But an intrahepatic cholestasis type of hyperbilirubinemia, in which conjugated bilirubin increases in the serum, is more usually encountered after major hepatectomy. We previously reported that this kind of hyperbilirubinemia was caused by alterations of the proportions of bilirubin subfractions in bile [1]. This abnormality was remarkable and persistent in the patients with prolonged hyperbilirubinemia.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…But an intrahepatic cholestasis type of hyperbilirubinemia, in which conjugated bilirubin increases in the serum, is more usually encountered after major hepatectomy. We previously reported that this kind of hyperbilirubinemia was caused by alterations of the proportions of bilirubin subfractions in bile [1]. This abnormality was remarkable and persistent in the patients with prolonged hyperbilirubinemia.…”
Section: Introductionmentioning
confidence: 92%
“…This type is more usually encountered after major hepatectomy. We have previously reported [1] that alterations in the proportions of bile bilirubin subfractions occurred after hepatectomy for bile duct cancer and it could be one of the causes of this kind of hyperbilirubinemia. Goresky et al [8] also reported similar alterations after liver transplantation which were manifest in the patients with rejection of the transplant.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation
“…Pre-operative changes in jaundiced patients consist of lower levels of pre-operative bilirubin diglucuronide (BDG) and higher levels of bilirubin monoglucuronide (BMG), corresponding to a lower BDG:BMG ratio and less efficient bile processing. Such modifications have been shown to be predictive of post-operative liver function after hepatic resections [3] , and furthermore liver resection per se exerts an additional influence on the normal production of biliary bilirubin subfractions, further decreasing BDG and increasing BMG from the 5th to the 21st post-operative day [59,60] . A significant correlation was also found with the energy state of the remnant liver [60] , confirming the importance of the hepatic ATP on the post-operative outcomes [43] .…”
Section: Liver Resectionmentioning
confidence: 99%
“…Some degree of liver failure is inevitable following major liver surgery and particularly formal resections, ablation of liver tissue and tumours and major biliary reconstructions, but unless resolution is rapid and uncomplicated, potentially serious complications are possible. This type of post-operative liver failure is characterized by a markedly elevated serum bilirubin, hepatic encephalopathy and the myriad sequelae of an impaired ability to synthe-size proteins [3] . Its incidence following hepatobiliary (HPB) surgery is estimated at 10-20% [4][5][6] , and it is associated with a high mortality rate.…”
Section: Introductionmentioning
confidence: 99%